Macrophage Electrophoretic Mobility (MEM) Test in Cancer: A Critical Evaluation - Field, E. J. (1973)
Of 464 patients with verified cancer tested, 463 have been correctly diagnosed by measuring their lymphocyte sensitization to encephalitogenic factor or cancer basic protein. One patient with very rapidly advancing cancer gave a negative result but was found to have marked general hyporeactivity of her lymphocytes of unknown cause. Leukaemia, advanced tuberculosis, asthma, sarcoidosis, systemic lupus erythematosus, and a number of rare conditions may interfere with a correct diagnosis. It is advisable to test guinea-pigs for spontaneous sensitization to encephalitogenic factor and to exclude some of the other conditions by testing for sensitization of the patient's lymphocytes to BSA and PPD.